Application and efficacy of the pubovesical complex-preserving technique in intrafascial laparoscopic radical prostatectomy: A propensity score-matched analysis - Zaisheng Zhu; Yiyi Zhu; Han Wu; Pengfei Zhou; Quanqi Liu; Jianyong Tong; Yueping Wang (PLoS ONE, 2026)
Purpose This study aimed to introduce the pubovesical complex preserving technique in intrafascial laparoscopic radical prostatectomy (PPLRP) and compare its efficacy with the conventional intrafascial laparoscopic radical prostatectomy (Intra-LRP). Materials and methods The clinical data of 475 cases who underwent PPLRP (n = 171) or Intra-LRP (n = 304) between 2012 and 2023 and were followed up for over 1 year were retrospectively analyzed. The baseline characteristics of the two groups were balanced using 1:1 propensity score matching. Lastly, Kaplan-Meier analysis and multivariable logistic regression were performed to assess survival rates and their influencing factors. Results After matching, 310 cases (155 cases each) were successfully matched. The median follow-up for the two groups was 45 and 47 months, respectively. The rate of positive surgical margins (PSM) was comparable between the two groups at 17.4% and 14.8% (p = 0.537), respectively. Moreover, Kaplan-Meier analysis revealed no significant difference in the biochemical relapse-free survival (bRFS) (p = 0.772), cancer-specific survival (CSS) (p = 0.507), and overall survival (OS)(p = 0.065) between the two groups. PPLRP was associated with earlier recovery of urinary control, as evidenced by higher continence rates 24 hours following catheter removal (p = 0.002), as well as at 1 month (p = 0.011), 3 months (p < 0.001), and 6 months (p = 0.020). Regarding sexual function, postoperative IIEF-5 scores were significantly higher in the PPLRP group compared to the intra-LRP group (p < 0.001), and the proportion of patients achieving satisfactory erections for sexual intercourse was 31.0% and 19.4%, respectively (p = 0.018). Finally, multivariate analysis identified surgical technique as the sole factor affecting urinary continence recovery (p = 0.001), while surgical technique (p = 0.042) and age (p = 0.050) were associated with sexual function recovery. Conclusion Compared with traditional Intra-LRP, PPLRP offered superior preservation of the pubovesical complex (PVC) and neurovascular bundle (NVB). Indeed, it facilitated early recovery of urinary continence and sexual function without increasing oncological risk. Besides, it can be feasibly implemented in hospitals equipped with conventional laparoscopic systems.